+0

If you have 6x(8x+6)+9(4x+3), how would you finish factorising this?

0
211
1

If you have 6x(8x+6)+9(4x+3), how would you finish factorising this?

Cananyone help?

Guest Mar 11, 2015

#1
+80875
+5

6x(8x+6)+9(4x+3)  =      factor a 2 out of the terms in the first parentheses

(6x)(2)(4x + 3) + 9(4x + 3)

12x ( 4x + 3) + 9 (4x + 3) =  ....(4x + 3)  is the common factor.....

(12x + 9) (4x + 3)  =    factor a 3 out of the terms in the first parentheses

3(4x + 3) (4x + 3) =

3 (4x + 3)^2

CPhill  Mar 11, 2015
Sort:

#1
+80875
+5

6x(8x+6)+9(4x+3)  =      factor a 2 out of the terms in the first parentheses

(6x)(2)(4x + 3) + 9(4x + 3)

12x ( 4x + 3) + 9 (4x + 3) =  ....(4x + 3)  is the common factor.....

(12x + 9) (4x + 3)  =    factor a 3 out of the terms in the first parentheses

3(4x + 3) (4x + 3) =

3 (4x + 3)^2

CPhill  Mar 11, 2015

16 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details